Asia Pacific perspectives on the second year of the COVID‐19 pandemic: A follow‐up survey. Issue 8 (30th July 2022) - Pawankar, Ruby; Thong, Bernard Yu‐Hor; Tiongco‐Recto, Marysia; Wang, Jiu‐Yao; Latiff, Amir Hamzah Abdul; Leung, Ting Fan; Li, Philip Hei; Lobo, Rommel Crisenio M.; Lucas, Michela; Oh, Jae‐Won; Kamchaisatian, Wasu; Nagao, Mizuho; et al.
Abstract: Background: The Coronavirus disease 2019 (COVID‐19) pandemic is currently in its third year. This follow‐up survey was commissioned by the Asia Pacific Association of Allergy Asthma and Clinical Immunology (APAAACI) Task Force on COVID‐19 to compare and contrast changes in the epidemiology, clinical profile, therapeutics and public health measures of the pandemic in the Asia Pacific region. Methods: A questionnaire‐based survey comprising 32 questions was electronically sent out to all 15 member countries of APAAACI using Survey Monkey® from 1 December 2021 to 28 February 2022. Results: Seventeen responses were received from 14/15 (93.4%) member countries and 3 individual members. Mild‐to‐moderate COVID‐19 predominated over severe infection, largely contributed by COVID‐19 vaccination programmes in the region. The incidence of vaccine adverse reactions in particular anaphylaxis from messenger ribonucleic acid (mRNA) vaccines was no longer as high as initially anticipated, although perimyocarditis remains a concern in younger males. Novel therapeutics for mild‐to‐moderate disease including neutralizing antibodies casirivimab/imdevimab (REGEN‐COV®) and sotrovimab (Xevudy®), anti‐virals Paxlovid® (nirmatrelvir and ritonavir) and Molnupiravir pre‐exposure prophylaxis for high‐risk persons with Tixagevimab and Cilgavimab (Evusheld) are now also available to complement established therapeutics (e.g., remdesivir, dexamethasone and baricitinib) for severe disease. In the transition to endemicity, public health measures are also evolving away from containment/elimination strategies. Conclusions: With access to internationally recommended standards of care including public health preventive measures, therapeutics and vaccines among most APAAACI member countries, much progress has been made over the 2‐year period in minimizing the morbidity and mortality from COVID‐19 disease.